RANCANG BANGUN SMARTHOME BERBASIS HAIWELL CLOUD SCADA MENGGUNAKAN ESP32 - Muhammad Rifky Al Faris; Denny Irawan (Universitas Muhammadiyah Gresik, 2024)
These days, there is a definite need for labor that is quicker, simpler, and more succinct as technology advances. The term